Genetic bases of deltamethrin resistance in the invasive tiger mosquito Aedes albopictus - A genomic travel around the world - (:unkn) unknown (My University, 2024)
The tiger mosquito Aedes albopictus can transmit arboviral diseases such as dengue, zika and chikungunya. This vector has a growing impact on arbovirus transmission in tropical regions, and its capacity to colonise temperate regions is now threatening public health worldwide. Although innovative control methods are being developed, chemical insecticides are still massively used to control this arbovirus vector. Pyrethroid insecticides such as deltamethrin are commonly used to control Aedes mosquitoes. However, the repeated use of chemical insecticides has led to the selection of resistance mechanisms in Ae. albopictus. Since its detection in the 2000s in Asia, pyrethroid resistance has increased rapidly in this species spreading to many regions such as the Indian Ocean, southern Europe and Africa. However, the genetic basis of resistance is still poorly understood in Ae. albopictus, and only a few resistance markers have yet been developed for monitoring purposes. Until alternative vector control tools or efficient vaccine strategies are widely implemented, understanding the genetic basis of pyrethroid resistance in this major vector species is critical for limit arbovirus transmission.This thesis aims at studying the genetic bases of deltamethrin resistance in Ae. albopictus. Five regions from which deltamethrin resistance is increasing or already established were studied: Southern Europe, the Indian Ocean, Central Africa and South-East Asia. To consider the local genetic diversity, one composite population was created for each region by mixing multiple field populations. Those composite populations were then selected with deltamethrin for a few generations to increase resistance alleles frequency. For La Réunion island where deltamethrin resistance is clearly established, field populations were also studied. Bioassays were used to compare deltamethrin resistance level across populations. Integrated transcriptomic and genomic analyses were then used
Keywords: African Research